A preliminary study on the regenerative construction project management concept for enhancing sustainability performance of the construction industry - Sertyesilisik, Begum (Informa UK Limited, 2016)
As the world's living conditions deteriorate despite the precautions undertaken, there is need to reduce the construction industry's footprint. This paper aims to establish the principles for regenerative construction project management (RCPM). The regenerative approach has been assimilated into the project management concept considering construction project management requirements of the regenerative constructions, their need to be kept alive and in harmony with their location adapting changes in technology throughout their entire life. The research reveals that the RCPM requires changes in the current construction project management with respect to: the feasibility and processes; designers', project managers' and communities' roles; scope, complexity and focus of construction project management; contracts; and supply chain and material industry. The RCPM concept introduced in this paper allows the introduction of new concepts. This paper contributes to the body of knowledge as it is the first preliminar...